Os planos diretores dos municípios lindeiros ao lago de Itaipu sob a ótica de cidades inteligentes e sustentáveis: uma análise com base nas NBR ISO 37120 e 37122 - Finger, Juliana Reck (2024)
The objective of this study was to analyze the convergences between NBR ISO 37120 – Indicators for Sustainable Cities – and NBR ISO 37122 – Indicators for Smart Cities – and the master plans of the municipalities bordering the Itaipu Lake. Through a qualitative, applied research with a documentary analysis approach and the use of the IRAMUTEQ software, 14 Municipal Master Plans (MMP) were analyzed. From the extraction of keywords from NBR ISO 37120 and 37122, the research conducted in the MMPs revealed a greater number of keywords related to NBR ISO 37120 than to NBR ISO 37122, indicating a stronger convergence with sustainability-related themes and an opportunity for development in intelligence-related themes. Among the municipalities bordering the Itaipu Lake, Guaíra and Terra Roxa exhibited the highest number of keywords, which may suggest that these municipalities are more aligned with the themes of NBR ISO 37120 and 37122. Through the analysis generated by IRAMUTEQ, it was possible to identify the classes derived from the corpus of the master plans of the municipalities bordering the Itaipu Lake. This analysis revealed five classes, which allowed the identification of the alignment of the master plans with the guidelines of the City Statute. When analyzing the classes generated in relation to NBR ISO 37120 and 37122, Class 4, renamed as Infrastructure and Sustainable Public Services, presented the highest number of related themes, encompassing ten areas: energy, sewage, solid waste, transportation, economy, telecommunications and innovation, education, sports and culture, population and social conditions, recreation, and health. Thus, it can be observed that the MMPs of the municipalities bordering the Itaipu Lake include terms related to NBR ISO 37120 and 37122 but present opportunities for improvement and expansion. To support these municipalities, a framework was proposed for the development and revision of master plans, aiming to increase the number of strategies and actions related to sustainability and intelligence, making the cities smarter and more sustainable.